Islamic Educational Reformation of Abdullah Ahmad in Education System in Indonesia - Uldiman, Uldiman; Kaema, Muhammad Tolal; Kenedi, Gusril; Arief, Asmaiwaty; Suanti, Linda; Mutathahirin, Mutathahirin (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Abdullah Ahmad's worked as a figure in the modernization of Islamic education by establishing two educational institutions in the form of private schools in 1915, namely the Adabiah School and Association of Islamic Teacher. This research explores the renewal of Islamic education carried out by Abdullah Ahmad in the education system in Indonesia, namely at Adabiah and Association of Islamic Teacher. This research uses qualitative methods with an individual life history approach. All data is collected through character biographies, literature, documents, and evidence of relics in terms of written and physical data. Data collection is carried out by collecting, reducing, and presenting data followed by conclusions. Overall, the results of the research show that there were four reforms in Islamic education carried out by Abdullah Ahmad in Adabiah. Then there are also four reforms in Islamic education at Association of Islamic Teacher. Meanwhile, the realization of Abdullah Ahmad's renewal of Islamic education in Adabiah prioritized the vision of creating a generation with civilized, ethical character in the content of akhlaqul karimah with faith and sincerity to shape the etiquette of the nation's generation and Association of Islamic Teacher. In contrast to Association of Islamic Teacher the dynamics Association of Islamic Teacher, which was founded from 1978-1983, developed, in 1988-1993 it began to decrease, then in 1993-1998 it began to increase again, entering the 2000s Association of Islamic Teacher began to decrease, both in terms of school quality and graduate, the number of students and the latest realization from Association of Islamic Teacher schools has also experienced a setback with a small number of students.